Treatment of Persistent Gross Hematuria with Tranexamic Acid in Autosomal Dominant Polycystic Kidney Disease - Qing Yao; Ming Wu; Jie Zhou; Meiyang Zhou; Dongping Chen; Lili Fu; Rongrong Bian; Xiaohong Xing; Lijun Sun; Xiaohong Hu; Lin Li; Bing Dai; et al. (Karger Publishers, 2017)
Background/Aims: In this retrospective study we aimed to compare the effect of tranexamic acid (TXA) vs etamsylate, two hemostatic agents, on hematuria duration in autosomal dominant polycystic kidney disease (ADPKD) patients with persistent gross hematuria. Methods: This is a retrospective study of 40 patients with ADPKD and macroscopic hematuria. 20 patients receiving TXA and snake venom blood clotting enzyme injection were compared with 20 matched patients receiving etamsylate and snake venom blood clotting enzyme injection. The primary outcome was hematuria duration and the secondary outcomes were blood transfusion requirements and adverse events. Results: The hematuria duration was shorter in the TXA group compared with the etamsylate group (4[3-5] d vs 7[6-10] d, P<0.001). The volume of blood transfusion tended to be less in the TXA group than in the etamsylate group (300±115 ml vs 486±195 ml, P=0.12), and the number of patients needing a blood transfusion also tended to be lower [20% (4/20) vs 35% (7/20), P=0.29]. TXA and etamsylate were equally well tolerated and no serious adverse events were observed in both groups. Conclusions: Our study indicates that TXA treatment was more effective than etamsylate in stopping bleeding in ADPKD patients with persistent gross hematuria.